Comparative evaluation of T-Loop with different amount of pre-activation curvatures in lingual orthodontics- A finite element study - Pooja Girsa; Ashish Kumar Singh; Sridhar Kannan; Nitin Arora; Abhita Malhotra (Journal of Oral Biology and Craniofacial Research)
Introduction: Three-dimensional analysis of the moment, force and M/F ratio generated at the anterior and posterior region of the T-loop in five different groups of pre-activation curvatures using the finite element method. Materials and method: In this study, the geometric model of maxilla was constructed using a CBCT scan. The bracket system simulated was of the STb lingual bracket system from Ormco (0.18slot) with specified tip and torque values of all maxillary teeth and the arch wire used was 0.016″x 0.016″ TMA (Ormco) for fabrication of T-loop with dimensions of 6 ​× ​2 ​× ​7 ​mm. There were five different models generated with pre-activation of: 20°,30°,40°,50° and 60° in T-loop. The software used for the post-processing of the model was ANSYS Workbench 19.2. Result: When the amount of pre-activation of T-loop increased there was an increase in the moment, force and M/F ratio in all the five groups in lingual biomechanics. Conclusion: Although, the M/F ratio depicts the type of movement that will take place is uncontrolled tipping in all the five pre-activation groups, clinically we should give pre-activation ranging from 30° to 60° in T-loop in lingual orthodontics.